Foramen Magnum Meningioma—The Attainment of the Intra-Arachnoidal Dissection: 2-Dimensional Operative Video. Issue 6 (8th September 2021) - Essayed, Walid Ibn; Aboud, Emad; Al-Mefty, Ossama
Abstract: Ventral foramen magnum meningiomas are a forbidding lesion. The stake is so high with a risk of devastating paralysis and respiratory failure. Careful preoperative clinical and radiological evaluation is necessary to implement the best treatment plan. Successful surgical intervention depends on paying high attention to minute details throughout the case, from intratracheal intubation to extubation. The neural head-on-neck position is critical to avoid further medullary compression at intubation and positioning. 1 Extensive neurophysiological monitoring, including somatosensory, motor, brainstem evoked potential, and cranial nerves, during the positioning and throughout the case, is extremely helpful to detect early signs of dysfunction. 1 To expose and access ventral tumors, partial condyle resection and vertebral artery transposition are invaluable techniques. 2, 3 Preservation and minute manipulation of the vital neurovascular structures at this junction that includes the medullar, anterior spinal artery, posterior inferior cerebellar artery, vertebral junction perforators, and lower cranial nerves are essential for good outcomes. This is achieved by microsurgical intra-arachnoidal dissection under high magnification and after debulking the tumor to establish that plane. 1, 3, 4 The demonstration of this technique is the purpose of this article. We demonstrate these surgical tenets applied to the resection of a large ventral foramen magnum meningioma extending from the midclivus to the C3 vertebral body level in a 54-yr-old female presenting with swallowing difficulties. The patient consented to the surgical intervention and the publication of her images. Image at 1:38 reprinted with permission from Al-Mefty O, Operative Atlas of Meningiomas . Vol 1, © LWW, 1998.